Fabrication of superhydrophobic self-cleaning manganese dioxide coatings on Mg alloys inspired by lotus flower. Issue 12 (15th August 2020) - Zang, Dongmian; Xun, Xiaowei; Gu, Zhandong; Dong, Jiaojiao; Pan, Ting; Liu, Mingjie
Abstract: Superhydrophobicity is evolutionarily adaptive to surrounding environment. Lotus flower is naturally occurring superhydrophobicity. Artificial self-cleaning materials function effectively on superhydrophobic surfaces so that water droplets bead up and roll off the surface taking the contamination particles away. Inspired by lotus flower, we have fabricated superhydrophobic Mg alloy surfaces using manganese dioxide (MnO2 ) microspheres encased in stearic acid shells. The prepared superhydrophobic Mg alloy surface provides exceptional self-cleaning ability in air and oil, and remains non-wetting even after dynamic water shear, or exposure to strong acid, strong base, and saline solutions as well as organic solvents showing excellent mechanochemical durability, with broad application prospect. Graphical abstract: Image 1